THE EFFECT OF SALES PROMOTION, LIFESTYLE, AND PRODUCT PRICE ON FASHION PRODUCTS BUYING INTEREST - Purnamasarie, Musticha; Sismanto, Adi (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
The purpose of this study is to determine effect of Sales Promotion, Lifestyle, and Product Prices on Fashion Products Buying Interest on Facebook and Instagram Social Networking Consumers at Niur Village, Sukaraja District of Seluma Regency. It also aims to find out the most dominant factor influencing buying interest upon fashion products. This research uses quantitative methods. The population in this study were 588 community members at Niur Village. Out of 588, 25% (147) of the population were made as study sample drawn by using purposive sampling method. The criteria for this research sample are consumers who have ever bought fashion products from a minimum of Rp. 150,000 thousand up to a maximum of Rp. 300,000 thousand.Based on the results of multiple linear regression, it was obtained the regression equation of Y = 5.575 + 0.287 (X1) + 0.251 (X2) + 0.533 (X3). The results of the study and the hypothesis show that sales promotion (sig α = 0.008 <0.050), lifestyle (sig α = 0.033 <0.050), and price of the product (sig α = 0.000 <0.050). They simultaneously significantly influenced the interest in buying fashion products. Partially the three variables of sales promotion, lifestyle, and product prices have a significant effect on buying interest in fashion products. We recommend that fashion product entrepreneurs or online shops can maintain product quality and prices to increase consumer buying interest through Facebook and Instagram social networks at Niur Village, Sukaraja District, Seluma Regency.Keywords: Sales promotion, Lifestyle, Product prices, Buying interes